Paths towards Food Self- Reliance: Community Food Councils - Morse, Ken (Maine Policy Review, 2011)
In this case study the author describes the development of a local community food council, “Healthy Oxford Hills,” and discusses how such organizations can work to rebuild local food systems.
Keywords: Maine; community food councils; local foods